Kaolinite Powder Catalyzed Stereoselective Conversion of Dialkyl-2-(1,1,3-trioxo-1,3-dihydro-2H-1,2-benzisothiazol- 2-yl)-3-(triphenylphosphoranylidene)succinates to Dialkyl- 2-(1,1,3-trioxo-1,3-dihydro-2H-1,2-benzisothiazol-2-yl)-2- butendioat - SHAJARI, NAHID; RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates by saccharin leads to vinyltriphenyl-phosphonium salts, which undergo an addition reaction with counter anion in CH2Cl2 at room temperature to produce corresponding stabilized phosphorus ylides. Kaolinite powder was found to catalyze conversion of the stabilized phosphorus ylides to corresponding electron-poor N-vinylated isothiazoles in solvent-free conditions at 100ºC in 1 h in fairly good yields.